1974
DOI: 10.1037/h0037250
|View full text |Cite
|
Sign up to set email alerts
|

Temporal limits of human information processing: A developmental study.

Abstract: A schematic model of the human information processing system is presented, and, within this framework, differences between adults and children in information processing limits are discussed. It is tentatively concluded that some irreducible maturational differences in processing rate are present, along with differences due to nonprocessing factors of incentive, motivation, attentiveness, and practice. The following areas of investigation of rapid information processing are discussed as they relate to reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
5

Year Published

1976
1976
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(68 citation statements)
references
References 55 publications
6
57
0
5
Order By: Relevance
“…On both ends of the lifespan, information processing approaches have related changes in performance in a number of tasks, from simple sensory-motor to more cognitive tasks, to a reduction/increase of neural noise in the sensorymotor system (e.g., Kail, 1997;MacDonald, Nyberg, & Bäckman, 2006;Li, von Oertzen, & Lindenberger, 2006;Plude, Enns, & Brodeur, 1994;Wickens, 1974). The change of the signal-to-noise ratio during childhood has been attributed to the progressive myelination of the axons in the central nervous system (e.g., Klingberg, Vaidya, Gabrieli, Moseley, & Hedehus, 1999;Paus et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…On both ends of the lifespan, information processing approaches have related changes in performance in a number of tasks, from simple sensory-motor to more cognitive tasks, to a reduction/increase of neural noise in the sensorymotor system (e.g., Kail, 1997;MacDonald, Nyberg, & Bäckman, 2006;Li, von Oertzen, & Lindenberger, 2006;Plude, Enns, & Brodeur, 1994;Wickens, 1974). The change of the signal-to-noise ratio during childhood has been attributed to the progressive myelination of the axons in the central nervous system (e.g., Klingberg, Vaidya, Gabrieli, Moseley, & Hedehus, 1999;Paus et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…If Wickens' (1974) model is adopted and the response selection mechanism considered bypassed on highly compatible tasks, and if we further suggest that a deficit at the level of response selection is of primary importance in schizophrenic performance, the apparently contradictory findings are resolved. This is also consistent with the extensive data presented by Broen (1968) indicating that the schizophrenic's cognitive deficit is primarily a difficulty in response selection rather than in sampling input.…”
Section: *Eight Conditionsmentioning
confidence: 99%
“…The idea of the slope as an inverse measure of channel capacity is therefore difficult to maintain. Wickens (1974) has recently suggested that, with high stimUlus-response compatibility or prolonged practice, the response selection stage is bypassed by a direct stimUlus-response association or link. Similarly, Welford (1968) has indicated that in such circumstances the .…”
mentioning
confidence: 99%
“…Newell (1976), however, suggests that trainee ability to process complex KR varies with age as well as the difficulty of the task. Younger trainees are less apt to be able to process complex KR (Farnham-Diggory, 1972;Wickens, 1974), and the more difficult the training task, the less likely it will be that trainees will have sufficient processing capacity available to take full advantage of highly precise KR, especially if the post-KR delay is short (see above). Thus, the RC trainer should not give highly precise KR during the training of difficult tasks until a moderate level of learning has been reached.…”
Section: Type Of Krmentioning
confidence: 99%